STUDY ON EXCESS PORE WATER PRESSURE CHANGES OF SATURATED SOFT CLAY SUBJECTED TO UNDRAINED UNI-DIRECTIONAL AND MULTI-DIRECTIONAL CYCLIC SIMPLE SHEARS - Nhan, Tran Thanh; Thien, Đo Quang (Vietnam Journal of Earth Sciences, 2014)
In this paper, normally consolidated specimens of kaolinite clay were tested under undrained uni-directional and multi-directional cyclic simple shears. It is shown from the test results that shear strain amplitude (γ), cyclic shear direction (phase difference (θ)) and the number of cycles (n) have significant effects on the changes of excess pore water pressure during cyclic shearing. However, the effect of cyclic shear direction on the excess pore water pressure can be eliminated by using a new parameter - cumulative shear strain (G*). Conventional estimation method of excess ore water pressure can not be used for the case of multi-directional cyclic shear with the number of cycles larger than 50 (n > 50). Consequently, a new estimation method, which is a function of cumulative shear strain was proposed. This method can be applied to various experimental conditions including uni-directional and multi-directional cyclic simples shear with different shear strain amplitudes and number of cycles. References Ansal, A., Iyisan, R. and Yildirim, H., 2001. “The cyclic behavior of soils and effects of geotechnical factors in microzonation”, Soil Dynamics and Earthquake Engineering, Vol. 21, No. 5, pp. 445-452. DeGroot, D. J., Ladd, C. C. and Germaine, J. T., 1996. Undrained multidirectional direct simple shear behavior of cohesive soil, J. Geotechnical Eng., ASCE, Vol. 122, No. 2, pp.91-98. Fukutake, K. and Matsuoka, H. A., 1989. “Unified law for dilatancy under multi-directional simple shearing”, Journal of JSCE Division C, JSCE, Vol. (412/III-1), pp. 143-151 (tiếng Nhật). Hyodo, M., Yamamoto, Y. and Sugiyama, M., 1994. “Undrained cyclic shear behaviour of normally consolidated clay subjected to initial static shear stress”, Soils and Foundations, Vol. 34, No. 4, pp.1-11. Matsuda, H., 1997. “Estimation of postearthquake settlement-time relations of clay layers”, Journal of JSCE Division C, JSCE, Vol. 568(III-39), pp. 41-48 (tiếng Nhật). Matsuda, H. and Ohara, S., 1989. “Threshold strain of clay for pore pressure buildup”, Proc. of 12h World Conf. on Soil Mechanics and Foundation Engineering, Rio De Janeiro, pp. 127-130. Matsuda, H. and Nagira, H., 2000. “Decrease in effective stress and reconsolidation of saturated clay induced by cyclic shear”, Journal of JSCE Division C, JSCE, Vol. 659(III-52), pp. 63- 75 (tiếng Nhật). Matsuda, H., Shinozaki, H., Okada, N., Takamiya, K. and Shinyama, K., 2004. “Effects of multi-directional cyclic shear on the postearthquake settlement of ground”, Proc. of 13th World Conf. on Earthquake Engineering, Vancouver, B.C., Canada, Paper No. 2890. Matsuda, H., Andre, P. H., Ishikura, R. and Kawahara, S., 2011. “Effective stress change and post-earthquake settlement properties of granular materials subjected to multi-directional cyclic simple shear”, Soils and Foundations, Vol. 51, No. 5, pp. 873-884. Ohara, S., Matsuda, H. and Kondo, Y., 1984. “Cyclic simple shear tests on saturated clay with drainage”, Journal of JSCE Division C, JSCE, Vol. (352/III-2), pp. 149-158 (tiếng Nhật). Ohara, S. and Matsuda, H., 1988. “Study on the settlement of saturated clay layer induced by cyclic shear”, Soils and Foundations, Vol. 28, No. 3, pp. 103-113. Ohmachi, T., Kawamura, M., Yasuda, S., 159 Mimura, C. and Nakamura, Y., 1988. “Damage due to the 1985 Mexico Earthquake and the ground conditions”, Soils and Foundations, Vol. 28, No. 3, pp. 149-159. Yasuhara, K. and Andersen, K. H., 1991. “Recompression of normally consolidated clay after cyclic loading”, Soils and Foundations, Vol. 31, No. 1, pp. 83-94. Yildirim, H. and Ersan, H., 2007. “Settlements under consecutive series of cyclic loading”, Soil Dynamics and Earthquake Engineering, Vol. 27, No. 6, pp. 577-585.